REDUKSI KECEMASAN MENGHADAPI UJIAN NASIONAL MELALUI ISLAMIC BRIEF COUNSELLING PADA SISWA - Enik Sartika (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
This study aims to describe the reduction of anxiety in facing the national exam through Islamic brief counseling to students. The discussion is carried out by way of deep thinking, with several theories that approach the meaning of anxiety and approaches taken to prevent anxiety behavior. The results of the study show that the Islamic brief counseling approach can reduce anxiety, including: (1) Conducting counseling with students and asking them to tell their problems briefly, then being directed to be aware of the hopes/wants they want to achieve So that students begin to think about solutions to problems. (2) Directing students to try to find self-awareness to focus on solutions and not on the problems experienced. So that students dare to face the problem. (3) Remind students that every test/difficulty will surely come with ease according to Allah's promise. (3) Make students aware that the human task is to try their best, and the results are in God's decree. This is to encourage students to always try.